2018
DOI: 10.1111/rda.13191
|View full text |Cite
|
Sign up to set email alerts
|

Association of interservice interval with conception rate in Japanese Black cattle

Abstract: This study aimed to clarify the association of interservice interval (ISI) with conception rate (CR) and to evaluate factors affecting ISI in Japanese Black cattle. Data used in this study covered 32,639 artificial insemination (AI) records on 972 farms. The mean ± SEM of ISI and CR was 57.0 ± 0.3 days and 44.6 ± 0.3%, respectively. The relative frequency of ISI differed significantly between parity groups (p < .05). For parity 0, the proportion of ISI at an 18- to 24-day interval was 43.6%, whereas the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…Resynchronization facilitates greater use of TAI, which is favourable to allow for cross‐breeding, replacement of genetically superior matrices, greater standardization of batches of calves and reduction in the amount of bulls needed. Our results along with the study by Irikura et al, (, ) suggest that future studies on resynchronization, followed by a third AI treatment under tropical conditions, could also aid in maximizing the reproductive efficiency.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Resynchronization facilitates greater use of TAI, which is favourable to allow for cross‐breeding, replacement of genetically superior matrices, greater standardization of batches of calves and reduction in the amount of bulls needed. Our results along with the study by Irikura et al, (, ) suggest that future studies on resynchronization, followed by a third AI treatment under tropical conditions, could also aid in maximizing the reproductive efficiency.…”
Section: Discussionsupporting
confidence: 75%
“…Previous research (Irikura, Uematsu, Kitahara, Osawa, & Sasaki, , ) showed an increase in pregnancy rate after a third artificial insemination (AI). Resynchronization facilitates greater use of TAI, which is favourable to allow for cross‐breeding, replacement of genetically superior matrices, greater standardization of batches of calves and reduction in the amount of bulls needed.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological observational studies are suitable for analyzing the factors that hinder productivity or reproductive performance [36]. There are several reports about Japanese Black cows [28, 29, 41]; however, very few reports have concretely elucidated such factors using dairy cows from a local prefectural unit in Japan.…”
mentioning
confidence: 99%
“…Because cattle grazing is not performed in this region, the calves were fed roughage such as rice straw, Italian ryegrass, oat straw, and a dietary concentrate twice daily. The average productivity for Japanese Black cattle has been previously reported [ 10 , 11 , 14 , 21 , 27 ].…”
Section: Methodsmentioning
confidence: 99%